2021
DOI: 10.3390/plants10040620
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the End-Use Quality Potential of a Collection of Spanish Bread Wheat Landraces

Abstract: Modern plant-breeding practices have narrowed the genetic base of wheat, such that there is a need to introduce new germplasms with underexploited diversity into breeding programs. Wheat landraces are a very valuable resource when searching for genetic variation, which not only possess increased adaptability, but also quality-related traits. Several studies have shown a wide genetic diversity in Spanish wheat landraces compared to other germplasm collections; therefore, the main objective of this study is to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 94 publications
(142 reference statements)
0
13
0
Order By: Relevance
“…To facilitate further discussion, a summary of the main findings of the marker-trait association study conducted on the diversity panel is presented in Table 3. It must be noted that the findings reported in López-Fernández et al (2021) on the effect of the genetic structure of the Spanish collection of bread wheat landraces on TKW, KS, GP and SVol support that no relationship exists between the differences among populations at GS2A noted above (Table 2) and the phenotypic variation in this germplasm panel.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…To facilitate further discussion, a summary of the main findings of the marker-trait association study conducted on the diversity panel is presented in Table 3. It must be noted that the findings reported in López-Fernández et al (2021) on the effect of the genetic structure of the Spanish collection of bread wheat landraces on TKW, KS, GP and SVol support that no relationship exists between the differences among populations at GS2A noted above (Table 2) and the phenotypic variation in this germplasm panel.…”
Section: Discussionmentioning
confidence: 64%
“…The diversity panel was formed by 187 Spanish bread wheat landraces that constituted the primary set from which the Spanish bread wheat core collection was developed (Pascual et al 2020a). The genetic structure and genomic variability of this collection was reported in Pascual et al (2020b) while its phenotypic characterization for some agronomic and quality traits was further described in López-Fernández et al (2021).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Similarly, the 1Ax2* and 1Ax1 subunits provide an improved food quality variation compared to 1Ax-null allele (Jiang et al, 2017). López-Fernández et al (2021) the Glu-B1 locus in the 189 Spanish landraces analysed, among which the allele i coding for HMW-GS 17+18 was found at a low frequency of 1.59%. The same tendency for this allele was described by Dai et al (2020) who found it in only spring forms of Chinese Xinjiang wheat landraces and historical cultivars.…”
Section: Resultsmentioning
confidence: 93%
“…With the objective of identifying the new sources of resistance in unexplored germplasm and new genomic regions for resistance to spot blotch, we used a diverse set of 294 wheat genotypes, including landraces, indigenous and exotic germplasm lines, advanced breeding lines, and popular wheat varieties of India. Landraces are well known as a repository for gene pools, sources of genetic variability, and a high potential for adaptation to specific environmental conditions [43][44][45], whereas other germplasm represents genetic variations used in various breeding programmes as sources of variations for multiple traits. This panel was expected to possess novel alleles for multiple traits, including spot blotch, and was thus selected for the present study.…”
Section: Discussionmentioning
confidence: 99%